The Role of Financial Literacy and Digital Financial Literacy in Non-Cash Payment Usage: Evidence from MSMEs in Salatiga, Indonesia - Fevriera, Sotya; Saraswati, Birgitta; Pertiwi, Angelita; Yiswi, Trivena; Hartanto, Siswo (Industrija, 2025)
The development of digital technology makes MSMEs/merchants adapt by applying it. The objective of this research is to study the effects of financial literacy, digital financial literacy, and characteristics of MSME owners/merchants or attributes of their business on the usage of non-cash payment methods by MSMEs/merchants in Salatiga City. Besides investigating the two concepts, this study also analyzes the influence of the characteristics of MSME owners/merchants and business characteristics. Data for this research is collected from a survey. The technique used to analyze is binomial regression which is combined with the backward elimination method. This research finds that the knowledge dimension of financial literacy, the attitude dimension of financial digital literacy, and the education level of MSME owners/merchants have a positive effect on the utilization of non-cash payment methods.